2011
DOI: 10.1017/s002211201000474x
|View full text |Cite
|
Sign up to set email alerts
|

Drop fragmentation on impact

Abstract: International audienceWe address the sequence of events accompanying the transition from an initially compact volume of liquid a drop into dispersed fragments when it impacts a solid surface. We describe the change of topology of the drop to a radially expanding sheet and discuss the reasons of its rim destabilization, responsible for the emergence of radial ligaments which ultimately fragment into smaller drops. The dynamics ruling the radius of the sheet, its stability and the resulting fragment drop size di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
202
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(243 citation statements)
references
References 45 publications
37
202
3
1
Order By: Relevance
“…This square-root dependence of the sheet radius on the Weber number is well-known for drop impact on solids in absence of friction (Villermaux & Bossa 2011). As Klein et al (2015) already showed, it is also in good agreement with experimental observations for a drop impacted by a laser.…”
Section: Problem Formulation and Solutionsupporting
confidence: 87%
See 1 more Smart Citation
“…This square-root dependence of the sheet radius on the Weber number is well-known for drop impact on solids in absence of friction (Villermaux & Bossa 2011). As Klein et al (2015) already showed, it is also in good agreement with experimental observations for a drop impacted by a laser.…”
Section: Problem Formulation and Solutionsupporting
confidence: 87%
“…This dynamics is similar to that following a mechanical impact such as on a solid substrate or a pillar, which has been studied thoroughly (see e.g. Clanet et al 2004;Yarin 2006;Villermaux & Bossa 2011;Kolinski et al 2012;Riboux & Gordillo 2014;Josserand & Thoroddsen 2016), including a few studies on the fragmentation of the drop (Villermaux 2007;Xu et al 2007;Villermaux & Bossa 2009, 2011Riboux & Gordillo 2014). A laser proves to be an adequate tool to vary the extension of the impact without arXiv:1512.02415v1 [physics.flu-dyn] 8 Dec 2015…”
mentioning
confidence: 94%
“…The same distribution has also been shown to provide a good model for the fragment sizes for liquid sheets resulting from the oblique collision of two cylindrical jets [29] and for an axisymmetric expanding sheet formed by the impact of a steady gravity-driven circular jet and droplet onto the horizontal upper surface of a solid cylinder [30,31]. The Γ distribution is…”
Section: (B) Spray Sizementioning
confidence: 88%
“…Sheet breakup is more complex than dripping. The time for the sheet to breakup can be estimated using linear stability theory [76,77]. Also, experiments and fluid dynamic models on atomization [78][79][80] relate the average size of drops to a power of a characteristic Weber number The terminology used for trajectory reconstruction is illustrated in Figure 7 and defined in Table 4.…”
Section: Sheet Breakupmentioning
confidence: 99%
“…Area of Convergence, Directionality [13] [ 5,97] Area of Origin [13,19,68 Backspatter Pattern; Forward Spatter Pattern area of origin, weapon [48] [5, 47,110,191] Blood Clot [6,162] [ 160 , 162] Bloodstain pattern area of origin, weapon [13,35,76 [ 166,170,196] Perimeter Stain time between drip and wipe-off, [155,197,198] [ 155,188] [188] [155,163,197,198] Flow Pattern [12,162,199] [12, 162,185,199] [185] [12] Impact Pattern weapon, motion; directionality [78][79][80]128] [5] [72,128,136] Insect Stain [157,200] Mist Pattern weapon, directionality [81, 154 , 186 Spatter Stain [201] [126, [15...…”
Section: Mixingmentioning
confidence: 99%